Penggantian Minyak OLTC Trafo 2 150 kV di Gardu Induk Rangkasbitung Baru PLN ULTG Rangkasbitung (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
PLN (Persero) is the state-owned company responsible for supplying electrical energy in Indonesia and plays a crucial role in ensuring the reliability and continuity of power distribution. Therefore, all electrical equipment, particularly power transformers, must be maintained in safe and reliable operating conditions. Transformers function to change voltage levels from high to low or vice versa and are essential components in the electric power distribution system. One important transformer component that requires periodic maintenance is the On Load Tap Changer (OLTC). To maintain transformer performance and extend its service life, routine maintenance activities such as OLTC oil replacement are necessary. PT. PLN (Persero) ULTG Rangkasbitung conducts regular OLTC oil replacement twice a year as part of its preventive maintenance program. Transformer oil serves as both an insulating medium and a cooling agent; therefore, its condition greatly affects transformer reliability and operational safety. Degraded oil quality can cause insulation failure and reduce transformer efficiency. This study aims to describe the procedure and implementation of On Load Tap Changer oil replacement at the transformer substation of PT. PLN (Persero) ULTG Rangkasbitung. The research method used is field research, carried out through direct observation and interviews with maintenance personnel. The results of this study are expected to provide a clear understanding of the OLTC oil replacement process, support proper maintenance practices, and emphasize the importance of transformer maintenance in ensuring the reliability and sustainability of the electric power system.